Reduced gonadotroph stimulation by ethanolamine plasmalogens in old bovine brains - Kadokawa, Hiroya; Kotaniguchi, Miyako; Kereilwe, Onalenna; Kitamura, Shinichi (Scientific reports, 2021)
Ethanolamine plasmalogens (EPls), unique alkenylacyl-glycerophospholipids, are the only known ligands of G-protein-coupled receptor 61—a novel receptor co-localised with gonadotropin-releasing hormone receptors on anterior pituitary gonadotrophs. Brain EPl decreases with age. Commercial EPl—extracted from the cattle brain (unidentified age)—can independently stimulate FSH secretion from gonadotrophs. We hypothesised that there exists an age-related difference in the quality, quantity, and ability of bovine brain EPls to stimulate bovine gonadotrophs. We compared the brains of young (about 26 month old heifers) and old (about 90 month old cows) Japanese Black bovines, including EPls obtained from both groups. Additionally, mRNA expressions of the EPl biosynthesis enzymes, glyceronephosphate O-acyltransferase, alkylglycerone phosphate synthase, and fatty acyl-CoA reductase 1 (FAR1) were evaluated in young and old hypothalami. The old-brain EPl did not stimulate FSH secretion from gonadotrophs, unlike the young-brain EPl. Molecular species of EPl were compared using two-dimensional liquid chromatography-mass spectrometry. We identified 20 EPl molecular species of which three and three exhibited lower ( P < 0.05) and higher ( P < 0.05) ratios, respectively, in old compared to young brains. In addition, quantitative reverse transcription-polymerase chain reaction detected higher FAR1 levels in the POA, but not in the ARC&ME tissues, of old cows than that of fertile young heifers. Therefore, old-brain EPl may be associated with age-related infertility.